Gerakan Revolusi Protein Hewani Dalam Upaya Pencegahan Stunting Berbasis Isi Piringku dengan Metode Pendampingan PMT Ibu Baduta di Belawan Sicanang - Sembiring, Elyani; Pasaribu, Dewi Astuti; Tumanggor, Lisnawati; Sirait, Lusiana Lusia; Utami, Nirma Surya (Universitas Methodist Indonesia, 2024)
Stunting is a growth and development process that can affect children from early pregnancy until the age of three or four, often caused by a lack of micronutrient intake. Foods that contain animal protein are very important to fulfill nutritional needs during child development, especially the first 1000 days of life (HPK). Eggs are a cheap, protein-rich and readily available animal food. Consuming these foods during this critical period can improve growth, cognitive ability, and nutritional status in children. The long-term impact of animal protein consumption, among others, improves nutritional status in under-fives. The purpose of the implementation of this community service is to increase the knowledge of mothers who have infants in Belawan Sicanang village about stunting prevention through a high animal protein revolution based on consuming animal protein every day through providing additional food in the form of milk and consumption of One Egg a Day (SALURI), diverse, nutritious, balanced and safe which is the contents of my plate. The output of this service project is an increase in knowledge among mothers who have infants at risk of stunting, as well as providing eggs and milk to 40 children at risk of stunting in the working area of the Belawan Sicanang village.